Perception of subjective well-being and negative and positive attitudes towards aging itself - Maya-Pérez, Eloy; Galindo-Soto, Jonathan Alejandro; López-Cervantes, Paola; Ramírez-Pérez, Dionisio (Horizonte Sanitario, 2022)
Objective: Analyze the perception of subjective well-being and negative and positive attitudes towards aging itself of older people in the municipality of Celaya, Guanajuato, Mexico. Material and Methods: This research is quantitative in nature, with a descriptive-transactional design. 167 older people participated, 104 women and 63 men over 60 years old, residents of the municipality of Celaya, Guanajuato. The participants reported not having cognitive impairment and were able to answer the items on the scales themselves. The following scales were used: PANAS questionnaire for positive and negative affect, Diener’s life satisfaction and GDS for abbreviated depression. Results: The study suggests a positive trend in relation to subjective well-being and negative and positive attitudes towards aging, in general the participants recognized experiencing positive affect in relation to their experiences, their family relationships, as a couple, their life experience, with the environment. It is important to highlight that the correlation between the positive and negative affectivity scales Pearson’s r value is 0.71, which indicates a direct correlation with an r² of 1. Conclusion: Based on the data provided by the study, it is stated that the perception of well-being about aging itself is identified through negative and positive attitudes. The latter being more significant because the participants recognize them as key elements to achieve a better adaptation to the circumstances of their own lives. Keywords: Affection, Aging, Mental health